The Therapeutic Benefits of Warm Compresses in Alleviating Menstrual Pain (Dysmenorrhea) among Young Woman - Siti Arifah; Beatrix Yenike Zangga; Luluk Khusnul Dwihestie (Journal of Public Health Sciences, 2023)
The aim of this study was to examine the effectiveness of warm compresses in reducing dysmenorrhea, or menstrual pain, among young women. A pre-experimental study was conducted on 30 female students of 7th-grade at SMPK Waimangura (a junior high school) using a One-Group Pre-test Post-test Design, with respondents selected through purposive sampling. The study used a numerical rating scale to gauge the level of menstrual pain, and the data was analyzed using the Wilcoxon test. Prior to applying warm compresses, most of the participants reported moderate pain, but after the application of warm compresses, the majority reported no pain. The results showed a significant effect of warm compresses in reducing menstrual pain, with a p-value of 0.000 (<0.05). Therefore, it is recommended that young women use warm compresses as a non-pharmacological method to alleviate menstrual pain by applying a clean towel-covered glass bottle for 15-20 minutes. This intervention is effective in reducing muscle spasms in the abdominal area, providing a sense of comfort, and reducing pain.